Emotional intelligence and pedagogical intuition - Yulia M. Garipova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
Teachers are increasingly faced with the need to act quickly, in today's environment. There are due, in particular, to the widespread emergency transition to distance learning. A key quality for the educator is mobility and the ability to make professional decisions quickly related to the development of pedagogical intuition. According to most scientists who have studied the phenomenon of intuition, in particular, A.S. Carmin and E.S. Haikin, intuition is seen as an experience of emotional perception of images. Therefore, this paper suggests that the development of intuition should be directly related to the development of emotional intelligence. A pilot study was carried out on Naberezhnye Chelny State Pedagogical University graduate students. The sample consisted of 50 young men and women, who were diagnosed using three methods: "Emotional intelligence" by J. Mayer, P. Salovey and D. Caruso; "Intuition in the structure of self-regulation of activity" by I.V. Vasilyeva and "Intuition ideas" by P.E. Grigoriev and I.V. Vasilyeva. As a result of the research, statistically significant results were obtained on two scales of the mentioned methods.